Long-Term Cultures of Spinal Cord Interneurons - Vargova, Ingrid; Kriska, Jan; Kwok, Jessica C. F.; Fawcett, James W.; Jendelova, Pavla (Frontiers in Cellular Neuroscience, 2022)
Spinal cord interneurons (SpINs) are highly diverse population of neurons that play a significant role in circuit reorganization and spontaneous recovery after spinal cord injury. Regeneration of SpIN axons across rodent spinal injuries has been demonstrated after modification of the environment and neurotrophin treatment, but development of methods to enhance the intrinsic regenerative ability of SpINs is needed. There is a lack of described in vitro models of spinal cord neurons in which to develop new regeneration treatments. For this reason, we developed a new model of mouse primary spinal cord neuronal culture in which to analyze maturation, morphology, physiology, connectivity and regeneration of identified interneurons. Isolated from E14 mice, the neurons mature over 15 days in vitro, demonstrated by expression of maturity markers, electrophysiological patch-clamp recordings, and formation of synapses. The neurons express markers of SpINs, including Tlx3, Lmx1b, Lbx1, Chx10, Pax2 The neurons demonstrate distinct morphologies and some form perineuronal nets in long-term cultivation. Live neurons in various maturation stages were axotomized, using a 900nm multiphoton laser and their fate was observed overnight. The percentage of axons that regenerated declined with neuronal maturity. This model of SpINs will be a valuable tool in future regenerative, developmental, and functional studies alongside existing models using cortical or hippocampal neurons.